Transatlantic Democracy in the Twentieth Century. Transfer and Transformation - Nolte, Paul (2016)
Transatlantic democracy in the 20th century - this concept goes beyond the idea of an American civilizing mission in Europe after two World Wars, and certainly beyond the notion of re-educating Germans, and making them fit for Western institutions after Nazism. As democracy is being contested anew in the beginning of the 21st century, a much more complicated landscape of democracy since 1900 emerges. Transfer was not a one-way-street, and patterns of conflict and transformation affected both American and European political societies. American democracy may not be reduced to a resilient defense of original traditions, while the narrative of German democracy is more than redemption from catastrophe. The essays in this volume contribute to a new history of transatlantic democracy that accounts for its manifold experiences and constant renegotiations, up to the current challenges of American and European populism